Rapunzel Syndrome: A Rare Postpartum Case - Teshome Tegene; Yahia Foda; Omar Hussain; Kolawole Oloniyo; Ngoc-Tram Ha; Geeta Manikonda (Case Reports in Gastrointestinal Medicine)
The Rapunzel syndrome describes a disorder in which a significant amount of hair is swallowed, forming a trichobezoar that extends past the stomach into the small intestines. Given the indigestible nature of hair, it subsequently leads to obstruction within the gastrointestinal system. Clinically, patients may present with symptoms of gastrointestinal obstruction, including abdominal complaints such as pain, nausea, vomiting, and diarrhea. However, due to its broad and nonspecific presenting symptoms, the diagnosis of Rapunzel syndrome warrants consideration once other common etiologies have been excluded. Surgical intervention is often required to remove the abdominal mass. This unusual syndrome is often associated with psychiatric disorders, affecting young women most commonly. In this report, we will discuss a unique case of Rapunzel syndrome in a one-month postpartum woman.